Efektivitas penambahan mobilisasi sendi dan pelatihan stabilisasi pada non-specific neck pain - Ni Komang Ayu Juni Antari; Anak Agung Gede Angga Puspa Negara; Ni Made Indri Sagita; Made Hendra Satria Nugraha (MEDIA ILMU KESEHATAN, 2022)
Background: Neck pain is a common complaint that often occurs in the community with a total prevalence of 86%. Non-specific neck pain cause problems such as: range of motion limitation, increased neck disability, and increased in the angle of forward head posture.Objective: The purpose of this study was to determine the effectiveness of adding joint mobilization and stabilization exercise to ultrasound therapy (UST) intervention and stretching exercise in reducing neck pain and disability in non-specific neck pain.Methods: This study is an experimental study with a randomized controlled trial group design. Study participants were randomly divided into two groups. The control group (n=14) was given UST + stretching exercise while the treatment group (n=14) was given UST + stretching exercise + joint mobilization + stabilization exercise. This study measures the effectiveness of therapy in terms of reducing pain as measured by a visual analogue scale, as well as neck disability with the Indonesian version of the Modified Northwick Park neck pain Questionnaire (MNPQ).Results: The results of the comparison test between groups showed that there was a significant difference (p<0.05) in the reduction in pain and disability scores between the control and treatment groups.Conclusion: The addition of joint mobilization and neck stabilization exercises to the intervention of ultrasound therapy and stretching training was more significant than the administration of ultrasound therapy and stretching training alone in reducing neck pain and disability in non-specific neck pain.